2007
DOI: 10.1007/s00216-006-0935-y
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of gamma irradiation as a stabilisation technique in the preparation of tissue reference materials for a range of shellfish toxins

Abstract: The effect of γ-irradiation on concentrations of hydrophilic and lipophilic phycotoxins has been investigated by use of HPLC-UV and LC-MS. Pure toxins in organic solvents and toxins in mussel (Mytilus edulis) tissues were irradiated at three different doses. In solution all toxin concentrations were reduced to some extent. Most severe decreases were observed for domoic acid and yessotoxin, for which the smallest dose of irradiation led to almost complete destruction. For pectenotoxin-2 the decrease in concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…With the increased use of LC-MS for multi-toxin monitoring, the need for a CRM certified for multiple groups of toxins has also increased. An international collaboration to produce a freeze-dried mussel tissue (Mytilus edulis) CRM (CRM-FDMT1) [11] was initiated following a series of feasibility studies [7,[11][12][13][14][15]. This Electronic supplementary material The online version of this article (doi:10.1007/s00216-016-0004-0) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…With the increased use of LC-MS for multi-toxin monitoring, the need for a CRM certified for multiple groups of toxins has also increased. An international collaboration to produce a freeze-dried mussel tissue (Mytilus edulis) CRM (CRM-FDMT1) [11] was initiated following a series of feasibility studies [7,[11][12][13][14][15]. This Electronic supplementary material The online version of this article (doi:10.1007/s00216-016-0004-0) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…The decision to proceed with the production of a wet tissue homogenate is strengthened when it is considered that this matrix is very similar to the type of wet shellfish samples generally received as part of routine regulatory monitoring programs. Feasibility studies showed that γ-irradiation was suitable as a stabilization procedure for use in the preparation of AZA RMs, and it was demonstrated that the treatment was highly effective in eliminating microbial activity in shellfish tissue RMs after they have been bottled [32]. Irradiation was therefore selected as a post-bottling stabilization process for CRM-AZA-Mus.…”
Section: Resultsmentioning
confidence: 99%
“…The bottles were transported on dry ice to the Agriculture and Agri-Food Canada facility in Ste-Hyacinthe (Quebec, Canada) for γ-irradiation. The irradiation dose received by all bottles was in the range of 14.3 to 19.4 kGy (γ-irradiation, source cobalt 60) [32]. The bottles were returned frozen to the NRCC in Halifax for sealing (12ASD Heat Sealer, Sentinal Packaging Inc., Hyannis, MA, USA) inside trilaminate lightproof foil pouches (Retort Pouches, ISE USA Inc).…”
Section: Preparation Of Crm-aza-musmentioning
confidence: 99%
“…Extracts were combined in 25 mL volumetric flasks and made up to the mark with extraction solvent [30]. OA group esters were determined using the base hydrolysis method [41].…”
Section: Lipophilic Toxin Extraction and Analysis (Oa And Aza Groups)mentioning
confidence: 99%
“…However, this method is inappropriate for the AZAs [29]. A feasibility study on gamma-irradiation showed that it was suitable for various toxin groups [30] . However, long-term stability information is not available for this treatment for many of the toxin of interest in this project.…”
Section: Introductionmentioning
confidence: 99%